2016
DOI: 10.3389/frobt.2016.00026
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Software Framework for Eye–Hand Coordination in Humanoid Robots

Abstract: We describe our software system enabling a tight integration between vision and control modules on complex, high-DOF humanoid robots. This is demonstrated with the iCub humanoid robot performing visual object detection and reaching and grasping actions. A key capability of this system is reactive avoidance of obstacle objects detected from the video stream while carrying out reach-and-grasp tasks. The subsystems of our architecture can independently be improved and updated, for example, we show that by using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Conventional approaches for visuomotor applications like vision-based grasping are usually modular. Each module is independent and expert-designed, e.g., [24]. Developmental robotics takes a different approach, relying on emerging abilities and learning of complex skills through interaction with .…”
Section: B Neural Approaches For Visually-guided Graspingmentioning
confidence: 99%
“…Conventional approaches for visuomotor applications like vision-based grasping are usually modular. Each module is independent and expert-designed, e.g., [24]. Developmental robotics takes a different approach, relying on emerging abilities and learning of complex skills through interaction with .…”
Section: B Neural Approaches For Visually-guided Graspingmentioning
confidence: 99%
“…Besides, there are several platforms for humanoids and other robots in studies reported in ref. [42][43][44]. Details of Pioner3-AT bender robotic platform are provided in ref.…”
Section: Architecture and Platforms For Cognitive Robot Researchmentioning
confidence: 99%
“…Conventional approaches for visuomotor applications like vision-based grasping are usually modular. Each module is independent and expert-designed, e.g., [24]. Developmental robotics takes a different approach, relying on emerging abilities and learning of complex skills through interaction with Fig.…”
Section: B Neural Approaches For Visually-guided Graspingmentioning
confidence: 99%